The PK–PD Relationship and Resistance Development of Danofloxacin against Mycoplasma gallisepticum in An In Vivo Infection Model - Zhang, Nan; Wu, Yuzhi; Huang, Zilong; Yao, Lihua; Zhang, Longfei; Cai, Qinren; Shen, Xiangguang; Jiang, Hongxia; Ding, Huanzhong (Frontiers in Microbiology, 2017)
Mycoplasma gallisepticum is the causative agent of chronic respiratory disease (CRD), a prevalent disease of poultry, which is responsible for significant economic losses in farms. Although several antimicrobial agents are currently recommended for the treatment and prevention of M. gallisepticum infections, investigations of M. gallisepticum have been hampered by their fastidious growth requirements and slow growth rate. As such, little work has been conducted concerning the PK/PD relationship and mechanisms of antibiotic resistance between antimicrobials against M. gallisepticum. In the present study, danofloxacin was orally administrated to the infected chickens once daily for 3 days by an established in vivo M. gallisepticum infection model. Not only the concentrations of danofloxacin in plasma and lung tissues were analyzed, but also the counting of viable cells and changes in antimicrobial susceptibility in air sac and lung were determined. The PK and PD data were fitted by WinNonlin to evaluate the PK/PD interactions of danofloxacin against M. gallisepticum. PCR amplification of quinolone resistance determining regions (QRDRs) and DNA sequencing were performed to identify point mutations in gyrA, gyrB, parC and parE of the selected resistant mutant strains. In addition, susceptibility of enrofloxacin, ofloxacin, levofloxacin, gatifloxacin and norfloxacin against these mutant strains were also determined. The PK profiles indicated that danofloxacin concentration in the lung tissues was higher than plasma. Mycoplasmacidal activity was achieved when infected chickens were exposed to danofloxacin at the dose group above 2.5 mg/kg. The ratios of AUC24/MIC (the area under the concentration-time curve over 24 h divided by the MIC) for 2 log10 (CFU) and 3 log10 (CFU) reduction were 31.97 and 97.98 L·h/kg, respectively. Substitutions of Ser-83→Arg or Glu-87→Gly in gyrA; Glu-84→Lys in parC were observed in the resistant mutant strains that were selected from the dose group of 1 and 2.5 mg/kg. MICs of danofloxacin, enrofloxacin, ofloxacin, levofloxacin, gatifloxacin and norfloxacin against the resistant mutant strains with a single mutation in position-83 were higher than that with a single mutation in position-87. These findings suggested that danfloxacin may be therapeutically effective to treat M. gallisepticum infection in chickens if administered at a dosage of 5.5 mg/kg once